Could conjunctivitis in patients with atopic dermatitis treated with dupilumab be caused by colonization with Demodex and increased interleukin‐17 levels?: reply from the authors. (2nd March 2018) - de Bruin‐Weller, M.; Graham, N.M.H.; Pirozzi, G.; Shumel, B.
Abstract : Linked Article: de Bruin‐Weller et al. Br J Dermatol 2018;178 :1083–1101 .